Systematic Review of Shari'ah Standards in Hotels: Marketing Mix Method - Rahman, Fahrurrozi; Taqwiem, Ahsani (ITB AAS INDONESIA Surakarta, 2024)
The marketing mix is something that is prevalent in the industrial world, and concentrated hospitality which is a service industry, attending halal tourism in West Nusa Tenggara requires the hotel industry to metamorphose in providing services that are in accordance with the Shariah provisions in an effort to sustain halal tourism, in its journey the Grand Madani hotel appeared with the official syari'ah hotel label, while Lombok Raya did not use the syari'ah label. This study reveals the implementation of marketing mix which is carried out by Grand Madani and Lombok Raya hotels with a focus on the discussion of marketing the mix using sharia standards in hotels. To answer the focus of the discussion, this study uses descriptive qualitative, in which data are collected through observation, interviews, and documentation techniques, data analysis is carried out from the beginning and continues to be done through research conducted because qualitative research is not related to quantitative research theory, Nevertheless, hotel guests do not mind if a hotel that contains non-Islamic things such as pictures, photos, paintings, beverages that are not halal labeled, as long as their core needs well fulfilled and comfortable.